2016
DOI: 10.1002/nau.23047
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of bladder contractility from intravesical pressure–volume measurements

Abstract: Aims To describe parameters from urodynamic pressure recordings that describe urinary bladder contractility through the use of principles of muscle mechanics. Methods Subtracted detrusor pressure and voided flow were recorded from patients undergoing filling cystometry. The isovolumetric increase of detrusor pressure, P, of a voluntary bladder contraction before voiding was used to generate a plot of (dP/dt)/P versus P. Extrapolation of the plot to the y-axis and the x-axis generated a contractility paramete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
36
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 18 publications
1
36
0
Order By: Relevance
“…The second is the shape and frequency content of an individual DO wave. Analysis of this second pattern group, better described as DO wave shape, is more complex, but methods of analysis that have been proposed are Fast Fourier Transform frequency analysis, high definition ultrasound of the bladder wall , and advanced analysis of the rate of muscle fibre contraction . Automated procedures need to be developed and validated before reliable classification of DO wave shape can be achieved.…”
Section: What Do We Know From Research?mentioning
confidence: 99%
“…The second is the shape and frequency content of an individual DO wave. Analysis of this second pattern group, better described as DO wave shape, is more complex, but methods of analysis that have been proposed are Fast Fourier Transform frequency analysis, high definition ultrasound of the bladder wall , and advanced analysis of the rate of muscle fibre contraction . Automated procedures need to be developed and validated before reliable classification of DO wave shape can be achieved.…”
Section: What Do We Know From Research?mentioning
confidence: 99%
“…In 1978, van Duyl et al suggested to use (dp/dt × 1/p) max as a detrusor contractility parameter in analogy to cardiac contractility assessment. Thus, Fry et al are misleading when presenting this as a new concept. Further, a variety of similar parameters using pressure gradients have been evaluated comprehensively on clinical urodynamic data and in animal experiments .…”
Section: Detrusor Contractilitymentioning
confidence: 99%
“…However, the determination of such contractility parameters, particularly from the pressure rise preceding flow at normal micturition and more so at stop‐tests and with detrusor overactivity yielded highly variable values, indicating that basic assumptions are not met and that it is not a true maximum isometric contraction . Unfortunately these most important shortcomings are not taken into account with respect to DCP …”
Section: Detrusor Contractilitymentioning
confidence: 99%
See 2 more Smart Citations